All-fiber spectral modulating device based on microfiber interferometer grown with tungsten disulfide. Issue 5 (2nd September 2020) - Luo, Meng; Yang, Xinghua; Teng, Pingping; Kong, Depeng; Liu, Zhihai; Gao, Danheng; Li, Zhanao; Wen, Xingyue; Yuan, Libo; Li, Kang; Copner, Nigel
Abstract: Here an integrated compact low-cost all-fiber optical spectrum control device based on a single fiber interferometer and tungsten disulfide is reported. Tungsten disulfide was deposited onto the surface of the non-adiabatic microfiber under the application of the radiation from an amplified spontaneous emission source. Next, the near-infrared light (NIR), which leaked through the strong evanescent field of the microfiber, excited the surrounding tungsten disulfide and generated heat due to the photothermal effect. Therefore, the phase shift of the interference spectrum was caused by the surrounding change in the refractive index (RI). In the experimental work at 1550 nm, a spectral shift equal to 0.8 nm was obtained following the use of a pump laser operating at 980 nm. In addition, the device can may be used as an all-optical switch with a modulation depth of 18.1%. The proposed tungsten disulfide-based all-fiber device has potential application in all-optical signal controllable devices.